Developing software for Symbian OS : a beginner's guide to creating Symbian OS v9 smartphone applications in C++ - Babin, Steve (Symbian Press., 2007)
Many problems encountered by engineers developing code for specialized Symbian subsystems boil down to a lack of understanding of the core Symbian programming concepts. Developing Software for Symbian OS remedies this problem as it provides a comprehensive coverage of all the key concepts. Numerous examples and descriptions are also included, which focus on the concepts the author has seen developers struggle with the most. The book covers development ranging from low-level system programming to end user GUI applications. It also covers the development and packaging tools, as well as providing.